Implementation of Nursing Management MAKP Method and Dosing Cards System to Reduce the Risk of Burnout in Nurses at Simpang Lima Gumul Kediri Regional General Hospital - Rahmania Ambarika; Heri Hermawati; Rita Sukmawanti; Pramitha Nayana Librata; Hary Indah Fibriany; Titik Isbandiyah (Universitas STRADA Indonesia, 2025)
Burnout is a psychological syndrome resulting from prolonged exposure to chronic stress, especially prevalent in high-pressure environments such as healthcare. Among the healthcare providers, such as nurse appear to be at a higher risk of burnout, which can have serious personal consequences (substance abuse, broken relationships, and even suicide), as well as serious professional consequences such as lower patient satisfaction, lower quality of care, and even medical errors which expense carers and hospitals considerable funds. We conducted a community service by identifying the leading factors that caused burnout among nurses at Simpang Lima Gumul Kediri General Hospital. We found that Burnout among nurses in Simpang Lima Gumul Kediri is intensified by some factors including excessive workload, overcrowding, and challenging non-physical work environments. We proposed two interventions the Professional Nursing Care Model (Model Asuhan Keperawatan Profesional, MAKP) and the Dosage Card System as strategies to mitigate burnout among nurses at Simpang Lima Gumul Kediri Hospital. Through a community service activity, socialization sessions were conducted with department heads, nurses, and service administrators, where pre-test and post-test were administered to evaluate understanding of the interventions. Findings suggest that these sessions effectively enhanced participants' knowledge of the MAKP and Dosage Card System, providing actionable insights into applying these methods in clinical settings to help alleviate nurse workload and reduce burnout. The participants also raised another option which is Timbang Terima Digital as a third potential tool for enhancing nursing efficiency and patient care quality.